Designing an effective training evaluation system for training prgrammes in Sarawak Timber Industry development corporation :an action research study - Juiata, Akaw (UNIMAS, 1998)
The purpose of this study was to design a training evaluation system using the Core Skills for Effectiveness and Change Training Programme (COSEC) in the Sarawak Timber Industry Development Corporation (STIDC) as a case study. The objective of this study was to design an effective evaluation system with appropriate evaluation strategies and techniques to measure the effectiveness of the COSEC training programme. This programme was identified as a core training programme for the support and operational employees by the State Human Resource Development Division in the Chief's Minister Department.